Rudolf Schlechter’s South-American Orchids VI. Schlechter’s ‘network’: Bolivia, Paraguay, Chile, Argentina, and Uruguay - Ossenbach, Carlos (Universidad de Costa Rica, 2021)
The sixth and last chapter of this series about Rudolf Schlechter’s South American network covers Bolivia, the last of the tropical Andean countries, and continues into the partly tropical and subtropical regions of South America: Paraguay, Chile, Argentina, and Uruguay. Although Bolivia has a high biodiversity and a large orchid flora, the remaining countries (except for parts of Paraguay and a small part of northern Argentina) have mostly terrestrial orchids and were historically visited only by a relatively few European botanists. The number of travellers mentioned in this chapter is therefore much lower than in previous ones. As in previous chapters, the biographies and accomplishments of these travellers are preceded by brief geographical and historical introductory outlines for each country. Again, a few figures, such as August Weberbauer, already mentioned in the last chapter, are omitted here.